Proses Pelaksanaan Penyelidikan Dan Penyidikan Terhadap Tindak Pidana Fidusia Di Polres Demak - Ahmad Iksan; Amin Purnawan; Lathifah Hanim (Jurnal Hukum Khaira Ummah, 2020)
In this research author wants make scientific work on fiduciary crimes, If the debitor which transfers goods or mortgaging goods which is a fiduciary guarantee without permission kreditor then the debitor may be subject to fiduciary crime, this research aims to determine: 1).How the role of investigator at the Demak Police station in cracking down on fiduciary crimes in the jurisdiction of demak2).what are the obstacles of an investigator at the Demak Police station in the investigation of fiduciary crime 3).overcoming obstacles in the investigation of fiduciary crime conducted by the investigator at the Demak Police station in the conduct of fiduciary investigation. Research methodology in scientific writing is with approach sosial legal research and the specifications in the study used are deskriftif research. Is intended to provide a detailed picture of the object that became the subject matter, at the Demak Police station handling of fiduciary crime investigation namely in criminal detective Unit tipidter Demak Police station.Keywords: investigations, crimes, Fiduciary